Rare Coexistence of Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency and Turner Syndrome: A Case Report and Brief Literature Review - Isabel Inácio; Joana Serra-Caetano; Rita Cardoso; Isabel Dinis; Alice Mirante (Galenos Yayincilik, 2023)
The coexistence of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency and Turner syndrome (TS) is rare. We report on a 6-year-old Portuguese girl with mosaic TS [45,XO(39)/47,XXX(21)] presenting with premature pubarche at the age of 5 years. Laboratory findings showed elevated 17-hydroxyprogesterone, dehydroepiandrosterone sulfate, androstenedione and total testosterone, and her sex-determining region Y (SRY) was negative. CYP21A2 gene analysis revealed two mutations (c.[844G>T]; [CYP21A2del]), consistent with the non-classical form of CAH. Complete deletion of CYP21A2 allele occurred de novo. At 6 years and 4 months, she presented with accelerated growth velocity and hydrocortisone at a dose of 5 mg/m2/day was initiated. This case highlights the need to perform global examinations looking for virilization signs in TS patients' follow-ups. It also supports the reported genetic combination of TS and CAH. Therefore, CAH should be kept in mind in TS patients with SRY negative and virilization signs, even in the absence of short stature.